CHINA’S INFLUENCE IN NEPAL: INDIA’S CONCERN - Kumar, Pardeep; Kumar, Navin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
China’s strategic cooperation with India’s neighbours in South Asia, particularly Nepal, has been a matter of concern for us. Nepal’s geographical position has both advantages and disadvantages. It is like a sandwich between two giants: China to the north and India to the south, and both of these forces are opposed to each other. Nepal keeps playing the game by bowing to the pressure of both. Observing them interact, Nepal is also increasing its capabilities. However, in recent years, China has adopted a strong diplomatic relationship with other South Asian countries besides India by providing economic and technical assistance. These states are playing the ‘China card’ by receiving such assistance from India. China wants to eliminate India’s traditional influence over these countries, but India has always believed that if its security is taken care of, then it has some tension with Nepal for its own security reasons. This is also because the relations between China and Nepal have become closer in recent years. Strategic relations between India and Nepal are in place, but due to the history and geography of both, Nepal’s dependence on India has started decreasing. Now it has become a permanent fact that China is putting pressure not only on Nepal but also on other countries in South Asia. These developments are harmful for India: not only are its close agreements with Nepal being affected, but India’s security is also being comprised due to the entry of outsiders in South Asia. Therefore, in this research paper, we will describe how Nepal has affected India’s foreign policy due to the influence of China and how the deepening relations between Nepal and China have distanced Nepal from India. What challenges can India face from these relations and is it also posing a threat to India’s security?